Better diagnostic accuracy of neuropathy in obesity: A new challenge for neurologists. Issue 3 (March 2018) - Callaghan, Brian C.; Xia, Rong; Reynolds, Evan; Banerjee, Mousumi; Burant, Charles; Rothberg, Amy; Pop-Busui, Rodica; Villegas-Umana, Emily; Feldman, Eva L.
Highlights: Specific combinations of neuropathy measures should be used to maximize performance in obese cohorts. More neuropathy measures have good test characteristics for distal symmetric polyneuropathy than for small fiber neuropathy or cardiovascular autonomic neuropathy. Large fiber measures are more highly correlated than small fiber measures. Abstract: Objective: To determine the comparative diagnostic characteristics of neuropathy measures in an obese population. Methods: We recruited obese participants from the University of Michigan's Weight Management Program. Receiver operative characteristic analysis determined the area under the curve (AUC) of neuropathy measures for distal symmetric polyneuropathy (DSP), small fiber neuropathy (SFN), and cardiovascular autonomic neuropathy (CAN). The best test combinations were determined using stepwise and Score subset selection models. Results: We enrolled 120 obese participants. For DSP, seven of 42 neuropathy measures (Utah Early Neuropathy Score (UENS, N = 62), Michigan Neuropathy Screening Instrument (MNSI) reduced combined index, MNSI examination, nerve fiber density (NFD) leg, tibial F response, MNSI questionnaire, peroneal distal motor latency) had AUCs ≥ 0.75. Three of 19 small fiber nerve measures for SFN (UENS, NFD leg, Sudoscan feet (N = 70)) and zero of 16 CAN measures had AUCs ≥ 0.75. Combinations of tests performed better than individual tests with AUCs of 0.82 for DSP (two parameters) and 0.84 for SFN (three parameters). Conclusions: Many neuropathy measures demonstrate good test performance for DSP in obese participants. Select few small fiber nerve measures performed well for SFN, and none for CAN. Significance: Specific combinations of tests should be used for research studies to maximize diagnostic performance in obese cohorts.